Spanish Cinema 1973-2010: auteurism, politics, scenery and remembrance - Pérez-Guerrero, Ana María (Historical Journal of Film Radio and Television, 2017)
While other scholars note the emphasis on Christian values in these films, McGregor argues more pointedly that the morals they depict illustrate and reinforce Catholicism in particular. The censorship efforts by the Legion of Decency and the PCA supported specific tenets of the Catholic faith, according to McGregor.
Keywords: WOS